THE INFLUENCE OF INTELLECTUAL CAPITAL, MANAGERIAL OWNERSHIP, AND RETURN ON EQUITY ON PRICE BOOK VALUE IN FOOD AND BEVERAGE COMPANIES LISTED ON THE BEI IN 2016-2021 - Nanda Putri Rahmawati; Nurullaili Mauliddah; Budi Wahyu Mahardhika (International Conference on Economics, Management, Business, and Accounting, 2024)
This research is entitled the influence of Intellectual Capital, Managerial Ownership, and Return on Equity on Price Book Value in food and beverage companies listed on the IDX in 2016-2021. There are nine samples with the research sampling method using a purposive sample technique. This data analysis used the Static Package for the Social Sciences (SPSS 26) program. The results of this research partially show that Intellectual Capital and Managerial Ownership have a significant effect on Price Book Value. Meanwhile, the Return on Equity variable had an insignificant impact on Price Book Value. Simultaneously, the results obtained from Intellectual Capital, Managerial Ownership, Return on Equity have a simultaneous and significant effect on Price Book Value.